2020
DOI: 10.1002/poc.4094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H‐bonds on acidity of deoxy‐hexose sugars

Abstract: The unusual monosaccharaides such as deoxy‐hexose sugars, including methyl‐pentose and aldo‐pentose, are promising and important sugars in life science. However, little research on H‐bond interactions in these systems has been reported. The aldo‐pentose has a proton instead of the CH2OH group on C5; conversely, methyl‐pentose has a CH3 group on C5. The aim of the present study is to investigate the role and nature of intramolecular H‐bonds on acidity of CH3‐pentose sugars (L‐fucose and L‐rhamnose) and aldo‐pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…for deoxy-hexose sugars [26]; 2.17-2.19 (Å) for α/β-D-mannose [24]; and 1.85-2.11 (Å) for α/β-Dglucopyranose and α/β-D-galactopyranose [45]. Accordingly, our calculated results are comparable with those reported in the references [24,26,[44][45][46].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…for deoxy-hexose sugars [26]; 2.17-2.19 (Å) for α/β-D-mannose [24]; and 1.85-2.11 (Å) for α/β-Dglucopyranose and α/β-D-galactopyranose [45]. Accordingly, our calculated results are comparable with those reported in the references [24,26,[44][45][46].…”
Section: Resultssupporting
confidence: 88%
“…Several theoretical methods have been used to investigate the structural and electronic properties of carbohydrate sugars to understand the nature of H-bonds interactions [24][25][26][27][28]. The present study aims to investigate the H-bonds formation and the orientation effects of five hydroxyl groups in the four rare sugars theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in good agreement with our previous works for other similar systems, where the results indicated that the intramolecular H‐bonds dramatically affect the stability of the deprotonated sugar forms. [ 61,62 ]…”
Section: Resultsmentioning
confidence: 99%